THE EFFECT OF TWO STAY-TWO STRAY TECHNIQUE ON SPEAKING ABILITY OF THE TENTH GRADERS AT MAU AL ANWARI IN THE ACADEMIC YEAR 2023-2024 - Wageyono; Ali Nur Dzikri; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2024)
This study evaluates the effectiveness of the Two Stay-Two Stray technique in improving the speaking skills of tenth-grade students at MAU Al Anwari the academic year 2023-2024. Data were collected through pre-tests and post-tests to measure changes in students' speaking abilities after the application of the technique. Analysis revealed that most students achieved post-test scores within the 41-60 range, with an average post-test score of 52.38. The T-test analysis showed that the T-test value (13.650) was higher than the T-table value (2.086), indicating that the difference between pre-test and post-test scores was statistically significant. These findings suggest that the Two Stay-Two Stray technique has a significant impact on enhancing students' speaking abilities. The technique not only improved students' speaking skills but also provided a more enjoyable learning experience, supporting student motivation and engagement in the classroom. This result aligns with Warsono and Hariyanto's (2012) view that cooperative learning methods, such as Two Stay-Two Stray, enhance student participation and create a positive learning environment. The technique proved effective in facilitating peer interaction, allowing self-assessment, creative expression, and the development of interpersonal relationships, making it a valuable method for improving speaking skills in English language teaching.